Studying human capital formation of students using computer software - S. V. Kotov; A. L. Blokhin (Вестник Северо-Кавказского федерального университета)
Introduction. In this article, we consider global approaches to the research and assessment of human capital formation and its role in the global educational system. We have explored the terms and definitions of digital education – the inseparable part of higher education. We have identified and analysed the essential connection between digital education and human capital. Goal. Our research objective is to analyse and introduce certain software and determine its efficiency in educational system. The article presents a list of principal criteria for formation of human capital, the latter required for complex assessment of a student's human capital formation. Materials and methods. We describe an original instruction for using the software application «Defining Individual's Human Capital Score» and the database «Dynamic Patterns of Human Capital Score» (intellectual products) in order to estimate a student's human capital formation. The research was tested at the Southern Federal University and based at the Academy of Psychology and Pedagogics among students in their first to fourth year of studies. Results and discussion. Using the data obtained from the software tests we studied the efficiency of applying individual learning path in human capital formation of students. All the results were saved in the database. Conclusion. As one of the methods for assessment of human capital formation, this software demonstrated its efficiency and considerable impact in pedagogical, psychological, economic, and cultural aspects. In the future it will encourage overall positive evolution of digital education and human capital in Russia and facilitate innovation, growing workforce productivity, and learning the necessary professional and managerial skills.